Habit control during growth on GaN point seed crystals by Na-flux method. (2nd November 2016) - Honjo, Masatomo; Imanishi, Masayuki; Imabayashi, Hiroki; Nakamura, Kosuke; Murakami, Kosuke; Matsuo, Daisuke; Maruyama, Mihoko; Imade, Mamoru; Yoshimura, Masashi; Mori, Yusuke
Abstract: The formation of the pyramidal habit is one of the requirements for the dramatic reduction of dislocations during growth on a tiny GaN seed called a "point seed". In this study, we focus on controlling the growth habit to form a pyramidal shape in order to reduce the number of dislocations in the c -growth sector during growth on GaN point seeds. High temperature growth was found to change the growth habit from the truncated pyramidal shape to the pyramidal shape. As a result, the number of dislocations in the c -growth sector tended to decrease with increasing growth temperature.